Analisis Perawatan Mesin Casting Melalui Pendekatan Total Productive Maintenance (TPM) - Sukirno, Sukirno; Achmadi, Fuad (Universitas Mercu Buana, 2021)
Some of the problems that often arise during the production process are problems with machine breakdowns, operator negligence, operator disobedience to the rules that have been set and even many operators deliberately ignore the application of SOPs on machines so that the production process will be hampered. In this study will use the TPM (Total Productive Maintenance) approach to increase the use of casting machines and labor at PT. Prima Alloy Steel Universal, Tbk. So that it can be seen how much loss in the production process by using the OEE (Overall Equipment Effectiveness) method which will eventually grow some suggestions for solutions to overcome the various problems that cause these losses. The results of the percentage calculation of availability between 24.22% - 95.37%, while the percentage results from the calculation of the value of performance efficiency ranged from 104.85% - 412.90%, and the results of the calculation of the value of the rate of quality were 91.27% - 97.82%. The effectiveness level of the four machines used in the line casting machine with the largest total time losses was the MT17 machine with a value of 1243.75 hours. Meanwhile, the machine with the smallest total time losses was the MT-16 machine with a value of 1205 hours. Meanwhile, the largest losses were rework losses with total time losses of 1441.25 hours and yield / scrap loss being the smallest with total time losses of 74 hours. To increase production effectiveness, operators should be given skill knowledge about signs of damage that may occur, especially in casting machine spare parts and mold strength. In addition, it is very necessary to conduct a production capability test and rearrange it regularly and continuously.